The ICAO Council as a Dispute Settlement Body: Theoretical and Practical Issues - D. V. Ivanov; V. G. Donakanian (Московский журнал международного права)
INTRODUCTION. Achieving the goals of international legal regulation of a particular area of inter-State relations depends mainly on the existence of an effective dispute settlement mechanism. In the field of international air law, such powers are attributed to the Council of the International Civil Aviation Organization (hereinafter - ICAO), established under the Convention on International Civil Aviation of 1944 (hereinafter – the Chicago Convention). The Council's activities in this area cannot be called fruitful. Since the establishment of ICAO in 1947, the Council has not issued a single decision on disputes that have been brought before it. States have proved to be reluctant to use the dispute settlement mechanism established under the Chicago system. This is mainly due to the imperfection of the relevant provisions of the Chicago Convention, which for many years have been the object of criticism in international legal doctrine. Moreover, the provisions of the Chicago Convention do not answer the question regarding the legal nature of the Council as a dispute settlement body and the limits of its competence. The issue of the Council's competence has been considered twice by the International Court of Justice of the United Nations (hereinafter - ICJ). The judgments issued by the ICJ have not, in our view, resolved the existing legal problems but instead have contributed to further ambiguity. Furthermore, this topic has become especially relevant in light of the fact that in March 2022 the Netherlands and Austria initiated a dispute settlement procedure in the Council under Article 84 of the Chicago Convention against Russia for the downing of Malaysian civil aircraft in 2014. In these circumstances, the Council's de facto role in resolving international civil aviation disputes needs to be clarified.   MATERIALS AND METHODS. This paper examines the provisions of the Chicago international legal regime governing dispute settlement in the Council. The authors also analyse the established State practice in the application of Chapter XVIII of the Chicago Convention. Particular attention is given to legal doctrine, where several international legal concepts emerge to resolve existing legal problems. The methodological basis consists of general scientific and special research methods, including analysis, synthesis, systematisation, as well as formal-legal, formallogical and critical-legal methods.   RESEARCH RESULTS. The Council as a dispute settlement body has a dual legal nature. This is reflected in the fact that in procedural terms the Сouncil is similar to international judicial bodies in many aspects, but a number of features concerning the composition of the Council and the opportunity to appeal the decision issued prevent it from qualifying as a judicial body. This calls into question the power of the Council to issue legally binding deci-sions and the existence of its jurisdiction per se. State and Council practice also confirms that the Council under Chapter XVIII of the Chicago Convention acts as a mediator, which contrasts with the recent decision of the ICJ on the Qatar Air Blockade case, under which the Council has jurisdiction. Moreover, the Chicago Convention provides sanctions for non-compliance with Council decisions, which does not allow the Council to be considered as a mediator. Equally controversial was the ICJ finding that the Council, in settling disputes arising from the Chicago Convention (the Transit Agreement or other treaties), could examine issues outside their scope.   DISCUSSION AND CONCLUSIONS. The unclear legal status of the Council as a dispute settlement body, which was promoted by the controversial decision of the ICJ on the Qatar Air Blockade case, makes the mechanism under Chapter XVIII of the Chicago Convention highly ineffective. It is doubtful that states, consistently seeking legal certainty, would initiate proceedings in the Council under the existing international legal framework. As a result of the analysis of international legal concepts that propose the modernisation of the Chicago Convention dispute settlement mechanism, the authors conclude that either the establishment of a permanent arbitral institution within the structure of ICAO or the modification of the text of Chapter XVIII of the Chicago Convention so that the ICAO Council would act only as a mediator would be the preferable options. The authors share the position of lawyers who point to the need to negotiate new universal international law norms in the field of air law.